Clinico-pathological features in amyotrophic lateral sclerosis with expansions in C9ORF72 - Cooper-Knock, Johnathan (Oxford University Press, 2012)
Intronic expansion of the GGGGCC hexanucleotide repeat within the C9ORF72 gene causes frontotemporal dementia and amyotrophic lateral sclerosis/motor neuron disease in both familial and sporadic cases. Initial reports indicate that this variant within the frontotemporal dementia/amyotrophic lateral sclerosis spectrum is associated with transactive response DNA binding protein (TDP-43) proteinopathy. The amyotrophic lateral sclerosis/motor neuron disease phenotype is not yet well characterized. We report the clinical and pathological phenotypes associated with pathogenic C9ORF72 mutations in a cohort of 563 cases from Northern England, including 63 with a family history of amyotrophic lateral sclerosis. One hundred and fifty-eight cases from the cohort (21 familial, 137 sporadic) were post-mortem brain and spinal cord donors. We screened DNA for the C9ORF72 mutation, reviewed clinical case histories and undertook pathological evaluation of brain and spinal cord. Control DNA samples (n = 361) from the same population were also screened. The C9ORF72 intronic expansion was present in 62 cases [11% of the cohort; 27/63 (43%) familial, 35/500 (7%) cases with sporadic amyotrophic lateral sclerosis/motor neuron disease]. Disease duration was significantly shorter in cases with C9ORF72-related amyotrophic lateral sclerosis (30.5 months) compared with non-C9ORF72 amyotrophic lateral sclerosis/motor neuron disease (36.3 months, P < 0.05). C9ORF72 cases included both limb and bulbar onset disease and all cases showed combined upper and lower motor neuron degeneration (amyotrophic lateral sclerosis). Thus, clinically, C9ORF72 cases show the features of a relatively rapidly progressive, but otherwise typical, variant of amyotrophic lateral sclerosis associated with both familial and sporadic presentations. Dementia was present in the patient or a close family member in 22/62 cases with C9ORF72 mutation (35%) based on diagnoses established from retrospective clinical case note review that may underestimate significant cognitive changes in late disease. All the C9ORF72 mutation cases showed classical amyotrophic lateral sclerosis pathology with TDP-43 inclusions in spinal motor neurons. Neuronal cytoplasmic inclusions and glial inclusions positive for p62 immunostaining in non-motor regions were strongly over-represented in the C9ORF72 cases. Extra-motor pathology in the frontal cortex (P < 0.0005) and the hippocampal CA4 subfield neurons (P < 0.0005) discriminated C9ORF72 cases strongly from the rest of the cohort. Inclusions in CA4 neurons were not present in non-C9ORF72 cases, indicating that this pathology predicts mutation status.